INSEMINASI BUATAN DENGAN SEMEN CAIR PENGGANTI PEJANTAN PADA KELOMPOK MITRA USAHA PETERNAK KAMBING DI KELURAHAN RUM KOTA TIDORE KEPULAUAN - Muhammad Ade Salim; Nursjafani (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The shortage of pempek male goats due to high slaughter makes it difficult for partner breeders to carry out natural mating. The alternative is to use artificial insemination technology as a substitute for male pempek. The purpose of this service activity is to help partners who have difficulty mating their goats naturally. Using the artificial vagina of goat ejaculate, a 2.5 year old male stud was accommodated, mixed with coconut water diluent mixed with 10% egg yolk. Liquid semen was inseminated in 8 female recipients who were in heat. After days 19, 20, 21 post IB, the female recipients were observed for symptoms of estrus (NRR1), = 3 (37.5%) and NRR2 4 tails (50%) out of a total of 8 female recipients. Pregnant female = 2(25%).